Vacuum-assisted biopsy to diagnose a pathological complete response in breast cancer patients after neoadjuvant systemic therapy - Heil, Jörg; Richter, Hannah; Golatta, Michael; Sinn, Peter (Annals of surgery, 2018)
An abstract is unavailable. This article is available as a PDF only.